X^2 = 9x + 6
x^2 - 9x - 6 = 0
use quadratic formula : (-b (+-) sqrt b^2 - 4ac) / (2a)
a = 1, b = -9, c = -6
now we sub
x = (-(-9) (+-) sqrt -9^2 - 4(1)(-6)) / 2(1)
x = 9 (+-) sqrt 81 + 24)/2
x = 9 (+-) sqrt 105) / 2
x = 9/2 + 1/2 sqrt 105 or x = 9/2 - 1/2 sqrt 105
Answer:
you will know because it you do the system of whatever thingy and there are no two dots in the same row and the line is straight in either a negative or positive slope at a diagonal the equation is linear and its a function.
Step-by-step explanation:
The image is an example of a linear equation that is both a function and positive lenear
Answer:
4x^2 − 4x −1 + 11 / x+1
Step-by-step explanation:
The answer is
4x^2 − 4x −1 + 11 / x+1
= 10 hole minus. U add the two halfs then ad the hole minus